The prognostic value of the XPC rs2228001 single nucleotide polymorphism in cholangiocarcinoma - Wang, Guanwu; Mantas, Anna; Liu, Dong; Al-Masri, Tarick M.; Lueong, Smiths Sengkwawoh; Siveke, Jens; Luedde, Tom; Ulmer, Tom F.; Amygdalos, Iakovos; Vondran, Florian W. R.; Lurje, Georg; Neumann, Ulf Peter; et al. (Liver international, 2025)
Background and Aims Cholangiocarcinoma (CCA) is one of the most prevalent primary liver malignancies with increasing incidence and mortality rates, particularly in Southeast Asia. Surgical resection is a primary therapeutic option offered to patients with localised disease. Unfortunately, early disease recurrence is common and robust tools for tailored patient-centric post-operative management and follow-up schemes are highly desired but currently lacking. To address this unmet clinical need, this study investigated the clinical utility of the single nucleotide polymorphisms (SNPs) in DNA repair genes (ERCC5 rs1047768, APEX1 rs1130409, PARP1 rs1805414, XPC rs2228001 and ERCC5 rs873601) and patient prognosis after curative intent surgery. Methods A cohort of 229 patients who underwent surgical treatment for intrahepatic (iCCA) and perihilar (pCCA) cholangiocarcinoma was examined. Kaplan-Meier and multivariable Cox regression analyses were used to assess the impact of these SNPs on recurrence-free survival (RFS), cancer-specific survival (CSS) and overall survival (OS). Results Within comprehensive multivariable analyses, the TT genotype of XPC rs2228001 was significantly associated with prolonged RFS (GG/GT = 1, HR = 0.50, p = 0.027), CSS (HR = 0.42, p = 0.018) and OS (HR = 0.31; p = 0.031) in iCCA. Similarly, in pCCA, the TT genotype of XPC rs2228001 was an independent prognostic factor for prolonged CSS (GG/GT = 1, HR = 0.48, p = 0.041). Conclusions These findings suggest that SNPs in DNA repair genes, particularly XPC rs2228001, play a crucial role in modulating the prognosis of CCA.
Zuerst veröffentlicht: 20. August 2025
Gesehen am 20.01.2026